Integrating popular education into a model of empowerment planning. Issue 3 (27th May 2017) - Bengle, Tara; Sorensen, Janni
Abstract: This research introduces popular education into a neighborhood planning process in a low-income community in Charlotte, NC. Residents and members of a community–university partnership participated in a two-day workshop at the Highlander Education and Research Center in Tennessee and engaged in popular education exercises there to explore neighborhood issues through a lens of structural inequality. Data include interviews, participant observations, and a focus group. This research adds to the literature on empowerment planning – an approach to urban planning that integrates popular education, participatory action research, and community organizing to increase local control of planning and community development efforts.